Photodegradation of 2,4-Dichlorophenoxy Acetic Acid on TiO2, ZnO and Fe2O3 by Sunlight - Dindar, Bircan; Seven, Ozlem (Asian Journal of Chemistry, 2010)
The photocatalytic degradation of 2,4-dichlorophenoxy acetic acid (2,4-D) in aqueous solution containing a suspension of titanium dioxide (TiO2), zinc oxide (ZnO) and ferric oxide (Fe2O3) was studied under sunlight or concentrated sunlight. As expected, in the presence of TiO2 and ZnO irradiated by concentrated sunlight, the rate of photodegradation of 2,4-dichlorophenoxy acetic acid was seen to be faster than that irradiated by direct sunlight. Its degradation was not observed in the absence of catalyst and in the dark. TiO2 and ZnO which possess more higher band gap energy than that of Fe2O3 are effective photosensitizer for the degradation of this pesticide under concentrated sunlight. The band gap energy of reddish brown Fe2O3 (2.2 eV) is lower than that of colourless TiO2 (3.2 eV) and ZnO (3.2 eV). Fe2O3 absorbs more longer wavelength of the sunlight than others, but it is not successful as a catalyst under visible light. The results of all UV absorbtion spectroscopy and HPLC analysis regarding products illuminated showed that the complete degradations of 2,4-dichlorophenoxy acetic acid containing ZnO and TiO2 were observed nearly 99 and 85 % only in 45 min under concentrated sunlight.